Włoski dystrykt przemysłowy — rekomendacje dla Polski - Figuła, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Methods for adapting the Italian model of industrial districts in Polish conditions are discussed. The main focus is placed on culture as a source of competitive advantage of regions. Cultural traits are reflected in such areas as human competences and passions, company organization and features, and the organization of production. These region specifics should be taken into account. The paper discusses the potential for wide application of the Italian model in Poland, in such areas as architecture, urban planning, industrial relations, and education
Keywords: dystrykt przemysłowy; okręg przemysłowy; przemysł; szkolnictwo zawodowe